(untitled) (Baghdad Science Journal, 2019)
Metal nanoparticles can serve as an efficient nano-heat source with confinement photothermal effects. Thermo-plasmonic technology allows researchers to control the temperature at a nanoscale due to the possibility of precise light propagation. The response of opto-thermal generation of single gold-silica core-shell nanoparticle immersed in water and Poly-vinylpyrrolidone surrounding media is theoretically investigated. Two lasers (CW and fs pulses) at the plasmonic resonance (532 nm) are utilized. For this purpose, finite element method is used via COMSOL multiphysics to find a numerical computation of absorption cross section for the proposed core –shell NP in different media. Thermo-plasmonic response for both lasers is studied. The heat profile of different nanostructures is estimated. The results revealed that the temperature distribution profile was varied due to changing in the relative volume fraction between the core and the shell of nanoparticle.